2012
DOI: 10.4103/2229-5070.97239
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of gastro-intestinal helminths in horses in the Sudano-Guinean climatic zone of Cameroon

Abstract: Background:It is important to understand the biology and health impact of parasites affecting horses in the Western highlands of Cameroon.Aim:to evaluate the prevalence and intensity of infection of gastrointestinal helminths in these animals.Materials and Methods:A total of 894 horses (367 males and 527 females), and aged ≤1 to ≥7 years old were examined. A parasitological investigation of faeces was carried out using two techniques: concentration method of Full Born Willis (flotation in saturated solution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 1 publication
3
5
0
3
Order By: Relevance
“…Some studies performed in other developing countries showed higher prevalence rate of infection. For instance, reported 50% in Ethiopia, (8) 47.50% in India (9) and 18.48% in Cameroon (10). Studies from other countries vary in the prevalence rate; in some regions of Germany, the prevalence rate of infection was 16.7% (11), 5% prevalence rate in Australia (12) and in Brazil (13).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies performed in other developing countries showed higher prevalence rate of infection. For instance, reported 50% in Ethiopia, (8) 47.50% in India (9) and 18.48% in Cameroon (10). Studies from other countries vary in the prevalence rate; in some regions of Germany, the prevalence rate of infection was 16.7% (11), 5% prevalence rate in Australia (12) and in Brazil (13).…”
Section: Discussionmentioning
confidence: 99%
“…Na Alemanha, Hinney et al (2011) e em Camarões, Lem et al (2012) relataram uma prevalência de 8,7% e 16,9% de ovos de Oxyuris nas fezes de equinos, respectivamente. Pesquisas de ovos de Oxyuris através do Método de Gordon; Whitlock evidenciaram que o percentual variou de 3% (FRANCISCO et al, 2009), na Espanha; 4.76% (OIL; SUBEDI, 2018), em Nepal; 2,8% (CHAPARRO- GUTIÉRREZ et al, 2018), na Colômbia; 1,2% (UMUR; AÇICI, 2009), na Turquia; 1,8% (TOLOSSA; ASHENAFI, 2013), na Etiópia.…”
Section: Resultsunclassified
“…Os estudos sobre prevalência de Oxyuris equi são escassos e em sua maioria a espécie não é o foco do estudo. Lem et al (2012) observaram uma prevalência de 16,94% em cavalos de Camarões, no continente africano. O diagnóstico foi realizado utilizando a técnica de flutuação fecal.…”
Section: Resultsunclassified